2005
DOI: 10.1134/1.2121817
|View full text |Cite
|
Sign up to set email alerts
|

Hall coefficient in heavy fermion metals

Abstract: Experimental studies of the antiferromagnetic (AF) heavy fermion metal YbRh2Si2 in a magnetic field B indicate the presence of a jump in the Hall coefficient at a magnetic-field tuned quantum state in the zero temperature limit. This quantum state occurs at B ≥ Bc0 and induces the jump even though the change of the magnetic field at B = Bc0 is infinitesimal. We investigate this by using the model of heavy electron liquid with the fermion condensate. Within this model the jump takes place when the magnetic fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…( 136) cannot be satisfied at sufficiently low temperatures T ≤ T crit because of the temperature-independent term S 0 . Hence, the second order antiferromagnetic phase transition becomes the first order one at T = T crit [183,184] as shown by the arrow in Fig. 40.…”
Section: The T − B Phase Diagram Of Ybrh 2 Si 2 Hall Coefficient And...mentioning
confidence: 92%
See 1 more Smart Citation
“…( 136) cannot be satisfied at sufficiently low temperatures T ≤ T crit because of the temperature-independent term S 0 . Hence, the second order antiferromagnetic phase transition becomes the first order one at T = T crit [183,184] as shown by the arrow in Fig. 40.…”
Section: The T − B Phase Diagram Of Ybrh 2 Si 2 Hall Coefficient And...mentioning
confidence: 92%
“…(137) that the discontinuity in the Hall coefficient is determined by the anomalous behavior of the entropy, which can be attributed to S 0 . Hence, the discontinuity tends to zero as r → 0 and disappears when the system is on the disordered side of FCQPT, where the entropy has no temperature-independent term [186]. We now turn to the magnetization which is determined by Eq.…”
Section: The T -B Phase Diagram Of Ybrh 2 Si 2 Hall Coefficient Andmentioning
confidence: 99%
“…Thus, the outstanding puzzle of HF compounds originating from their universal behavior, which drastically differs from the behavior of ordinary metals and superconductors, is resolved [14][15][16][17]23,25], and the fundamental physics of HF compounds are controlled by the topological FCQPT (see, e.g., [15][16][17]20,27]). It is plausible to probe the other properties of HF compounds, which are not directly determined by the effective mass M * and cannot be explained within the framework of theories based on conventional quantum phase transitions (see, e.g., [15,20,24,[28][29][30][31]). An important feature explained within the framework of the FC theory is the crossover from NFL behavior to LFL behavior under the application of magnetic field B, pressure P, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the same reason, the residual resistivity ρ 0 (B) under the application of magnetic field B is strongly reduced, and the behavior of the resistivity ρ(T) changes from ρ(T) ∝ T to ρ(T) ∝ T 2 [17,32]. Moreover, the dependence of the magnetic field on the Hall coefficient R H (B) provides information about the QCP, determining the properties of HF metals [31]. Experiments have shown that the Hall coefficient R H (B) in the antiferromagnetic HF metal YbRh 2 Si 2 in magnetic fields B undergoes a jump in the zero-temperature limit under the application of magnetic field B, tuning the metal from the antiferromagnetic to the paramagnetic state at B = B c0 [33].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the Hall coefficient experiences a sharp jump because R H (B) ∝ 1/p 3 F in the AF phase and R H (B) ∝ 1/p 3 f in the paramagnetic phase. Assuming that R H (B) is a measure of the Fermi momentum [37,39] (as is the case with a simply connected Fermi volume), we obtain [7,40]…”
mentioning
confidence: 99%